Condroma de laringe: apresentação atípica - Sá,Leonardo C. B. de (2006)
The authors report a case of laryngeal chondroma , a rare benign larynx tumor in the cricoid and arytenoid cartilages. There are aproximately 250 cases previously described in literature. A male, 41 year-old patient, presented a severe and progressive dyspnea leading to tracheostomy. Direct microlaryngoscopy revealed arytenoid enlargement and subglottic stenosis and the endoscopical biopsy was inconclusive, since the tumor present a hard gnistency. We performed surgical excision by laringofissura and total resection of the tumor, with good result. The histopathological examination showed a chondroma with no malignance.